1975
DOI: 10.3758/bf03212939
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic influences on visual memory

Abstract: The Whorf-Sapir hypothesis has raised considerable controversy in the literatures of psychology and anthropology. Several misconceptions of the hypothesis are reviewed, and the hypothesis was experimentally supported in a visual reproduction paradigm. Subjects were first given label training for a set of figures, and were then asked to recall by drawing the shapes. Training with categorized labels resulted in a 25% improvement in recall when compared to a condition with nonword (paralog) labels. Even stronger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Ellis, 1968;Hardin & Banaji, 1993) and philosophical debate (Sutton, 2002). For example Santa and Baker (1975) showed that adults' free recall of nonsense shapes was facilitated when, at encoding, the stimuli were paired with verbal labels rather than nonwords; recall was assessed by asking participants to draw the shapes. Further, the verbal labels affected the sequence of free recall, such that the shapes were organised into clusters determined by the semantic categories of the words.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellis, 1968;Hardin & Banaji, 1993) and philosophical debate (Sutton, 2002). For example Santa and Baker (1975) showed that adults' free recall of nonsense shapes was facilitated when, at encoding, the stimuli were paired with verbal labels rather than nonwords; recall was assessed by asking participants to draw the shapes. Further, the verbal labels affected the sequence of free recall, such that the shapes were organised into clusters determined by the semantic categories of the words.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the verbal labels affected the sequence of free recall, such that the shapes were organised into clusters determined by the semantic categories of the words. Santa and Baker (1975) suggested that the memorial benefit of verbal labels is due to their focusing attention on distinctive stimulus features and establishing a range of associations that determine what is recalled and how (in what order). In addition to highlighting the 'organization and retrieval effects of language' (p. 449), Santa and Baker's (1975) findings also indicate that adults can use the language from encoding to organise nonverbal recall in the absence of the scaffolding provided by the objects present in re-enactment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, narrative reports have provided much valuable data in the study of naturalistic memory (e.g., G. Cohen, Conway, & Maylor, 1994;Marian & Neisser, 2000). However, tests that elicit and record nonverbal, perceptual content or productions from memory appear very rarely in research on memory for naturally occurring events (e.g., Martin & Jones, 1998;Rubin & Kontis, 1983;Swanson, Reffel, & Trahan, 1991), and in basic experimental studies of memory (e.g., Amrhein & Sanchez, 1997;Santa & Baker, 1975). Yet many events, especially television commercials and other complex everyday occurrences, have numerous nonverbal, visual features that eliciting verbal responses alone may not assess completely.…”
Section: Nonverbal Memory In Basic and Applied Researchmentioning
confidence: 99%